Are we doing too many instrumental deliveries in theatre?. (16th November 2010) - Tower, CL; Caine, N; Vause, S
Abstract : Background: The Royal College of Obstetricians and Gynaecologists (RCOG) provides guidance on which instrumental deliveries should be performed in theatre: malpositions, baby>4000 g, midcavity and a body mass index>30 kg/m 2 . The number of instrumental deliveries performed in theatre is reported to be increasing but reasons for this are unclear. Methods: The authors investigated trials in theatre for 1 year in a tertiary referral centre (October 2008–September 2009). Data were prospectively collected using an audit proforma that also served as medical documentation. Results: The total number of instrumental deliveries was 552 and 221 (40%) were conducted in theatre. Vaginal delivery was achieved in 209/221 (94.5%) of theatre cases. There was malposition in 140/221 cases (63%) and 205/221 (97%) were midcavity by RCOG definitions. Delivery was achieved using a non-metal cup ventouse in 34/221 (15%) of cases. In 202/221 (91%) a senior trainee (ST6-7) or consultant was present. Babies delivered in theatre were larger; median birthweight 3550 g interquartile range (IQR) 3100–390 0 g vs median birthweight 3200 g, IQR 2822–3600, p<0.01 Mann–Whitney U test). Theatre deliveries were also associated with a higher median blood loss of 450 ml, IQR 300–600 ml compared to 350 ml, IQR 300–500 ml, p<0.01 Mann–Whitney U test. Conclusion: A high proportion of instrumental deliveries (40%) are being conducted in theatre in our unit but most were midcavity or rotational, and conducted with senior staff present. This is likely to reflect increasing adherence to RCOG guidelines and fear of litigation. It may also imply an increasing complexity of the obstetric population, for example increasing obesity, and has implications for service provision on UK maternity units.